2014
DOI: 10.1097/acm.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Licensing Examination Performance and the Outcomes of Care by International Medical School Graduates

Abstract: These findings provide evidence for the validity of Step 2 CK scores. Given the magnitude of its relationship with patient outcomes, the results support the use of the examination as an effective screening strategy for licensure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 14 publications
4
80
0
4
Order By: Relevance
“…Performance in these examinations predicts performance in clinical practice and other medical assessment processes11 18, 19. For example, each part of the MRCP examination predicts the next17, and candidates who score higher in all parts of the MRCP examination do better in workplace‐based assessments than those who underperform16.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in these examinations predicts performance in clinical practice and other medical assessment processes11 18, 19. For example, each part of the MRCP examination predicts the next17, and candidates who score higher in all parts of the MRCP examination do better in workplace‐based assessments than those who underperform16.…”
Section: Discussionmentioning
confidence: 99%
“…Since then researchers have tried to establish such a link. Both Norcini et al (2014) and Tamblyn et al (2007) found correlations between licensing examination performance (in the USA and Canada respectively) and subsequent specific patient outcomes [38], or rates of complaints [39]. However, as discussed in more detail below, this evidence for a correlation with other variables is not supported by evidence for better patient outcomes as a consequence of NLEs.…”
Section: Resultsmentioning
confidence: 99%
“…Although the aforementioned studies by Norcini et al [38] and Tamblyn et al [39] demonstrate excellent arguments for the importance of testing, and medical education more generally, their findings are limited to establishing correlations between testing and outcomes and not causation. In other words, there is evidence that better doctors do better in NLEs, but not that doctors improve as a consequence of introducing NLEs; this kind of before and after evidence is absent in the extant literature.…”
Section: Resultsmentioning
confidence: 99%
“…This will require an emphasis on a robust, programmatic approach to assessment that ideally focuses on workplace-based formative assessment, rather than isolated high-stakes point in time-summative examinations. This is not to imply that there is not a role for high-stakes examination, as it can be useful to predict future patient outcomes [24], but rather that the opportunity for lower-stakes, more frequent assessment may be invaluable for learning on an ongoing basis [51]. Moving up to Miller's top level of "Does" (Fig.…”
Section: Shifting the Assessment Paradigm For Competency-based Educationmentioning
confidence: 98%